The new world : latvian monthly magazine for literature and art in Meerbeck : authorised by military government and UNRRA. (Meerbeck : Hugo Skrastins, 1946)
Bibliotheek Camille Huysmans
Cultuurtijdschrift van Letse emigranten in Duitsland
UNRRA staat voor: United Nations Relief and Rehabilitation Administration
Engels
Periodiek
Keywords: exilliteratuur; cultuur; emigranten; Letland